The decolonization of imagination : culture, knowledge, and power - Pieterse,Jan Nederveen & Parekh,Bhikhu ( Editors) (Oxford University Press, 1995)
The Decolonization of Imagination paves the way for a truly global cultural politics. Acknowledging that both the West and the former colonized have been shaped by colonial imaginaries, the book explores a wide range of cultural decolonization strategies. A distinguished cast of contributors, from both North and South, looks at the relations between culture and power, domination and the imagination in a variety of contexts.